2022
DOI: 10.3389/fmicb.2022.1017372
|View full text |Cite
|
Sign up to set email alerts
|

Finding the best combination of autochthonous microorganisms with the most effective biosorption ability for heavy metals removal from wastewater

Abstract: The presence of heavy metals (HMs) in the environment represents a serious environmental problem. In this regard, this work was conceived with the aim of finding, among indigenous microorganisms, the species and their combinations with the best biosorption activity for the following HMs: zinc, lead, cadmium, copper, and nickel. The experiment was carried out in several steps: (1) isolation and identification of microbial strains from the Central Effluent Treatment Plant’s wastewater; (2) studying the interacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 64 publications
0
6
0
Order By: Relevance
“…Moreover, P. aeruginosa strain CCM 3955 overexpresses a flagellin matrix that causes the agglomeration of silver NPs to avoid direct contact, which is bactericidal ( 25 ). K. oxytoca shows high resistance to diverse metals, including Zn, and robust biofilm formation in wastewater ( 29 ), providing a plausible explanation to the persistence of this bacterium in handwashing reservoirs and its ability to cause disease in immunocompromised individuals in contact with these environmental sources. It is also important to explain that the MIC and MBC concentrations of Zn NPs that inhibited and killed planktonic bacteria were the same, because the XTT reduction assay and CFU determinations typically correlate, even though either approach measure different parameters, such as metabolic activity and viability.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, P. aeruginosa strain CCM 3955 overexpresses a flagellin matrix that causes the agglomeration of silver NPs to avoid direct contact, which is bactericidal ( 25 ). K. oxytoca shows high resistance to diverse metals, including Zn, and robust biofilm formation in wastewater ( 29 ), providing a plausible explanation to the persistence of this bacterium in handwashing reservoirs and its ability to cause disease in immunocompromised individuals in contact with these environmental sources. It is also important to explain that the MIC and MBC concentrations of Zn NPs that inhibited and killed planktonic bacteria were the same, because the XTT reduction assay and CFU determinations typically correlate, even though either approach measure different parameters, such as metabolic activity and viability.…”
Section: Discussionmentioning
confidence: 99%
“…A similar study was conducted by Jakovljević et al. ( 2022 ) on the absorption of several metals by the biofilm of some individuals and combinations of microorganisms. The results showed that the Pb and Cd absorption by S. cerevisiae alone and K. oxytoca/S.…”
Section: Resultsmentioning
confidence: 52%
“…odorifera/S. cerevisiae combination was above 95% after 10 days (Jakovljević et al., 2022 ). Therefore, in future studies, the metal biosorption in SMG using biofilm can be investigated.…”
Section: Resultsmentioning
confidence: 99%
“…Jakovljević et al [ 30 ] studied the relationship between microorganisms and their ability to form biofilms to biosorb zinc, lead, cadmium, copper, and nickel. Inès et al [ 31 ] demonstrated the potential use of newly identified lipopeptides produced by Bacillus mojavensis BI2 for the bioremediation of heavy metals in contaminated water.…”
Section: Discussionmentioning
confidence: 99%